(untitled) (قضايا سياسية, 2023)
The technological and information revolution has led to the emergence of cyberspace as an area of competition and conflict between international and regional powers, which prompted the emergence of the concept of electronic or cyber warfare. The latter is carried out through electronic attacks and the control of computers, information, electronic networks and information infrastructure. Some see cyper wars as part of future wars, and they are no less dangerous than conventional wars, in terms of the threat they pose, and the size of the destruction they can lead to, given the high speed, wide spread, and the fact that they are implemented in ways that are often difficult to follow.